Analisa Perkembangan Struktur Aluminum (AC2B) dengan Pengaruh Penambahan Stronsium pada Part Transmisi Sub Assy Menggunakan Metode Pengecoran Gravity Dies Casting - Antonius, Dikky; Budiarto, Budiarto; Atmadi, Priyono; Pratama, Rakha Anugrah (Rekayasa Mesin, 2019)
Recently, one of the problems faced by the automotive industry is the frequent failure parts produced by casting processes such as uncomplete filling, low mechanical properties, shrinkage (non-uniform shrinkage), and porosity. In this research, the modification method with the addition of strontium while aluminum being melted is held. This experiment was made to solve either the shrinkage problem or porosity. The improvement of the mechanical properties of aluminum also become one of the purposes of the experiment. The concentration of strontium added was 0 wt.% Sr, 0.005wt.% Sr, 0.0075wt.% Sr, and 0.01 wt.%. The results show that the increased Sr content on AC2B will increase the mechanical properties, while the optimum value occurred by addition value 0.01wt. % Sr. However the results also show that the concentration of strontium has no effect on reducing shrinkage porosity, and can reduce the size of aluminum dendrites.